EVALUASI PENGAWASAN KEGIATAN BONGKAR MUAT BARANG DI PELABUHAN MAKASSAR - Murbayani Murbayani (AkMen JURNAL ILMIAH, 2014)
This study aims to determine the condition monitoring stevedoring activities conducted by the Traffic and Transport Marine Affairs and Port Office Administrator Makassar port affairs. The study population was all employees of Traffic and Transport Sector and port affairs Sea Port Administration Office of Makassar, amounting to 40 people, plus 105 head of Team Work (KRK) unloading personnel and 19 supervisors from the stevedoring company (PBM), with a standard error of 5%, obtained a total sample of 112 people. To analyze the data from this study the data analysis technique used is the analysis of quantitative data where the data processing will be done through descriptive statistical methods. Will take into account the above, the data processing techniques in the study conducted by the tabulation of data that results will be stated in the form of a frequency distribution table in the form of a percentage. From these results it can be concluded that the surveillance conducted by the Traffic and Transport Sector Sea and port affairs Makassar Port Administration Office of the activities of loading and unloading of goods can be described as follows: Preventive Monitoring Traffic and Transport Sector Sea and port affairs of the loading and unloading of goods generally are adequate primary on the rules that are used by supervisors unloading. Inadequate preventive surveillance, among others, the determination of position, duties, authority and responsibilities of regulatory authorities unloading. Field supervision of repressive Traffic and Transport Sea and port affairs of the activities of loading and unloading of goods is generally good because it is generally always done like checking the suitability of the number of workers unloading, checking the unloading of labor discipline. Repressive surveillance unfavorable due to lack of conformity checks carried out, among others, labor quality loading and unloading, as well as examination of the suitability of the number of loading and unloading facilities.